The Palgrave Handbook of Africa and the Changing Global Order
XXIII, 1129 p. 46 illus., 37 illus. in color.
Keywords: This handbook fills a large gap in the current knowledge about the critical role of Africa in the changing global order. By connecting the past, present, and future in a continuum that shows the paradox of existence for over one billion people, the book underlines the centrality of the African continent to global knowledge production, the global economy, global security, and global creativity. Bringing together perspectives from top Africa scholars, it actively dispels myths of the continent as just a passive recipient of external influences, presenting instead an image of an active global agent that astutely projects soft power. Unlike previous handbooks, this book offers an eclectic mix of historical, contemporary, and interdisciplinary approaches that allow for a more holistic view of the many aspects of Africa’s relations with the world. Samuel O. Oloruntoba is Adjunct Research Professor, Institute of African Studies, Carleton University, Ottawa, ON, Canada and President, African School of Governance and Policy Studies, Pretoria, South Africa Toyin Falola is Professor in the Department of History at the University of Texas at Austin, USA.